Constraint Analysis In Backyard Poultry Farming: A Study In Thiruvannamalai District Of Tamil Nadu - Rajendran , R.; Premavalli , K. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was conducted to find out the constraints in backyard poultry farming in five randomly selected villages of Thiruvannamalai district of Tamil Nadu. The information provided by farmers was analyzed by Rank Based Quotient (RBQ) method. Predation was perceived as a very serious constraint followed by damage to field crops, quarrel with neighbours and loss due to diseases. The non-disease issues should also be taken into consideration while formulating programmes targeting backyard poultry and necessary remedial measures be taken to address these problems.